The effect of phosphorylation on arrestin–rhodopsin interaction in the squid visual system. (28th October 2015) - Robinson, Kelly A.; Ou, Wei‐Lin; Guan, Xinyu; Sugamori, Kim S.; Bandyopadhyay, Abhishek; Ernst, Oliver P.; Mitchell, Jane
Abstract: Invertebrate visual opsins are G protein‐coupled receptors coupled to retinoid chromophores that isomerize reversibly between inactive rhodopsin and active metarhodopsin upon absorption of photons of light. The squid visual system has an arrestin protein that binds to metarhodopsin to block signaling to Gq and activation of phospholipase C. Squid rhodopsin kinase (SQRK) can phosphorylate both metarhodopsin and arrestin, a dual role that is unique among the G protein‐coupled receptor kinases. The sites and role of arrestin phosphorylation by SQRK were investigated here using recombinant proteins. Arrestin was phosphorylated on serine 392 and serine 397 in the C‐terminus. Unphosphorylated arrestin bound to metarhodopsin and phosphorylated metarhodopsin with similar high affinities ( K d 33 and 21 nM respectively), while phosphorylation of arrestin reduced the affinity 3‐ to 5‐fold ( K d 104 nM). Phosphorylation of metarhodopsin slightly increased the dissociation of arrestin observed during a 1 hour incubation. Together these studies suggest a unique role for SQRK in phosphorylating both receptor and arrestin and inhibiting the binding of these two proteins in the squid visual system. Invertebrate visual systems are inactivated by arrestin binding to metarhodopsin that does not require receptor phosphorylation. Here we show that squid rhodopsin kinase phosphorylates arrestin on two serines (S392, S397) in the C‐terminus and phosphorylation decreases the affinity of arrestin for squid metarhodopsin. Metarhodopsin phosphorylation has very little effect on arrestin binding but does increase arrestin dissociation. Abstract : Invertebrate visual systems are inactivated by arrestin binding to metarhodopsin that does not require receptor phosphorylation. Here we show that squid rhodopsin kinase phosphorylates arrestin on two serines (S392, S397) in the C‐terminus and phosphorylation decreases the affinity of arrestin for squid metarhodopsin. Metarhodopsin phosphorylation has very little effect on arrestin binding but does increase arrestin dissociation.